Exercise for optimizing bone health after hormone-induced increases in bone stiffness - Hughes, Julie M.; Guerriere, Katelyn I.; Popp, Kristin L.; Castellani, Colleen M.; Pasiakos, Stefan M. (Frontiers in Endocrinology, 2023)
Hormones and mechanical loading co-regulate bone throughout the lifespan. In this review, we posit that times of increased hormonal influence on bone provide opportunities for exercise to optimize bone strength and prevent fragility. Examples include endogenous secretion of growth hormones and sex steroids that modulate adolescent growth and exogenous administration of osteoanabolic drugs like teriparatide, which increase bone stiffness, or its resistance to external forces. We review evidence that after bone stiffness is increased due to hormonal stimuli, mechanoadaptive processes follow. Specifically, exercise provides the mechanical stimulus necessary to offset adaptive bone resorption or promote adaptive bone formation. The collective effects of both optimize bone strength during youth and preserve it later in life. These theoretical constructs provide physiologic foundations for promoting exercise throughout life.